Analisis Ragam Qirā’at dan Implikasinya terhadap Penafsiran - Sofian Effendi (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2021)
This paper tries to analyze the influence of the various Qirā’at on the Tafsīr of Al-Jāmi 'Li Ahkām Al-Qur’ān by Imam Al-Qurţubī, the extent to which the Qirā’at implications in this interpretation are in determining the law or helping in interpreting verses that have variant Qirâ' at various. The author finds that al-Qurţubī is quite intense in presenting various Qirā’at to support or explain a verse, not only specifically Qirā’at Mutawātir, even sometimes Qirā’at Shādhah sometimes Qirā’at Mudrāj also he displays to explain the meaning of the verse, even though he does not always use it as one of the tools for establishing the law or choosing which opinion is the most correct from the interpretation through the different Qirā’at variants. Quite contrary to the majority of scholars of the Malikī's madhhab says that the Qirā’at which is not Mutawātir cannot be used as a tool for legal stipulation from the verse of law, this writing also serves as an anti-thesis as well from the opinion of most scholars that Qirā’at Shādhah refuses to use it as a tool for hujjah, however, an Al-Qurţubī Dāred to violate the opinion of the majority of Malikī's madhhab.